WHEN THE GANGA DESCENDS: A Posthuman Exploration of a Religious Myth toward Planetary Sustainability - Soman, Dona (Journal of Dharma, 2022)
Human beings’ moral understandings and accepted social roles are located within a community’s central epistemological, metaphysical, and cultural paradigms. This paper explores the trajectory of Ganga myth from the ancient belief systems to its present manifestations in the contemporary world of ecological catastrophe. The ancient myth of the river Ganga and her descent to the earth’s surface tends to overcome the human-nonhuman dichotomy underlining the posthuman idea of patterns of continuity. Through mythical representations, narratives like Ma Ganga and the Razai Box bring forward negotiations on species interconnection, environmental ethics, and sustainability issues. The paper examines how holistic worldviews propagated by Indian mythology inspire reverence, reciprocal partnership, sustainability, and responsibility towards planetary development and wellbeing.